2020
DOI: 10.1007/s00170-020-05448-x
|View full text |Cite
|
Sign up to set email alerts
|

A cold forging process for producing thin-walled hollow balls from tube using a plastic insert

Abstract: This paper investigates a cold forging process for producing hollow balls made of an aluminium alloy. The forging with an outside diameter of 30 mm is formed from a tube section with a 2-mm wall thickness. Preliminary tests have shown that in traditional die forging, the use of a billet with such a small relative thickness not only limits the range of applicable geometric parameters but also causes buckling. The authors propose to solve this problem by using an additional tool that has an active effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…The primary objective of experimental testing is to verify and validate the numerical model. It is worth mentioning that similar studies were successfully conducted and their results were reported in previous works [7,19]. Moreover, results presented in this paper are a continuation of previous studies.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…The primary objective of experimental testing is to verify and validate the numerical model. It is worth mentioning that similar studies were successfully conducted and their results were reported in previous works [7,19]. Moreover, results presented in this paper are a continuation of previous studies.…”
Section: Methodssupporting
confidence: 88%
“…An interesting technological solution for hollow balls is a forging process performed with the use of flexible inserts. This technique was proposed by Samołyk et al [19]. A general scheme of this concept is shown in Fig.…”
Section: Popular Forming Methods For Hollow Ballsmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative to hydroforming is forging with the use of special elastic or plastic inserts. One example of such processes is the forging of hollow balls with the use of a low-melting alloy core to affect the inner wall of the workpiece [39].…”
Section: Introductionmentioning
confidence: 99%